Absurdity in Madurese and English Drama: A Comparative Study - Ulva Heryanti Rahmani; Siti Hanifa (Jurusan Sastra Indonesia, 2022)
Comedies of different countries have their own absurdities. Absurdity is something that human often experience for searching the meaning of life. Therefore, a comparative study of literature is used in this study to compare absurdities in the comedy originating from Madura and England. The objective of this study is to find out how the absurdities are shown in the Madurese and English comedy. Then, the method of this study is qualitative method. The sources of the data of this study are Juragan Hadroh and Gara-Gara Tukang Cukur EDAN!! by Sukur CS that were performed in 2021 and are compared to George Bernard Shaw’s Too True To Be Good that was performed in 1949. This study uses theory of absurdity that can be called “the philosophy of the absurd” by Albert Camus. The data of this study are in the form of characters utterance, narrator narrations, and gestures. This study found that both of Madurese and English comedies are existed as the form of searching for the meaning of life. Absurdities that are shown by Madurese and English comedies start from the names of characters, utterances and acts of the characters.